TINDAK TUTUR ILOKUSI USTAZ YUSUF MANSUR DALAM ACARA WISATA HATI DI STASIUN TELEVISI ANTV - Mei Reza Oktaviani; Hasnah Faizah AR; Auzar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research discussed the act of speech ilocution of Ustaz Yusuf Mansur in the event of heart tour in ANTV television station. The objective of this research was to described the act of speech ilocution of Ustaz Yusuf Mansur in the event of heart tour in ANTV television station. The method used was descriptive method with qualitative approach. In this research, was used three techniques that were refer technique, record technique and note technique. The data source was presentation of lecture video of Ustaz Yusuf Mansur in the tour heart event in ANTV television station. The data of this amount to 65 speeches, from the result of tour heart event in ANTV television. This research found there were five forms of speech acts ilocution, namely assertive, directive, expressive, declarative, and comissive.Key word : the act of speech ilocution, the form of speech acts of ilocution, the form of speak strategy